Effects of the Fuel Species on the Combustion Pressure in a Two Staged Fueled Scramjet Combustor - Hironobu Nishiguchi; Masatoshi Kodera; Sadatake Tomioka (Aerospace)
Two-staged fuel injection configuration for scramjet combustors has been shown to be effective in distributing heat release in the combustor for preventing the unstart transition of the engine by suppressing peak pressure while increasing the pressure thrust. In this study, the effect of fuel species on combustion characteristics in a two-staged fueled scramjet combustor was investigated. Wall pressure measurements in a two-staged fueled scramjet combustor were conducted in a combustion wind tunnel facility with fuels having different reactivity, such as H2 and CH4. Reynolds-Averaged Navier–Stokes/Large Eddy Simulation (RANS/LES) hybrid simulations were performed to verify the interaction characteristics between the primary and secondary combustion zones for different fuels. The experimental results confirmed that pressure peaks at injections were clearly separated in the hydrogen case, while these interacted with each other in the methane case with a lower reactivity than H2. The RANS/LES Hybrid analysis predicted this effect of fuel reactivity on the pressure distribution, namely, the heat release delay of the first stage fuel caused the interaction with the second stage fuel heat release. The results indicate that the need to design the staged fueled combustor, i.e., the injection stage interval accordingly to the reactivity of the fuel.